Global employment : an international investigation into the future of work - Simai, Mihály; Moghadam M., Valentine; Kuddo, Arvo (London Tokyo : Zed Books United Nations University, 1995)
Bibliotheek François Vercammen
Engels
Meerdelige publicatie
Keywords: werkgelegenheid